Answer:
32
Step-by-step explanation:
8 x 4 = 32
I'm pretty sure
Answer:
x = ![\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D)
Step-by-step explanation:
Since you cannot subtract -1 from 4x, you multiply 2 × 4x = 8x
Now, you have 8x - 1 + 3 = 7
Seperate the 8x from the other numbers
8x = 1 - 3 + 7 ---> 6
8x = 6
Now simplify
x =
<----- to reduce, divide the numerator and denominator by 2
Hence,
x = ![\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D)
Answer:
![x=1,y=3,z=1](https://tex.z-dn.net/?f=x%3D1%2Cy%3D3%2Cz%3D1)
Step-by-step explanation:
![4x-4y+4z=-4](https://tex.z-dn.net/?f=4x-4y%2B4z%3D-4)
![4x=-4+4y-4z](https://tex.z-dn.net/?f=4x%3D-4%2B4y-4z)
![x=-1+y-z](https://tex.z-dn.net/?f=x%3D-1%2By-z)
Substitute
into second equation:
![4\left(-1+y-z\right)+y-2z=5](https://tex.z-dn.net/?f=4%5Cleft%28-1%2By-z%5Cright%29%2By-2z%3D5)
![-4+4y-4z+y-2z=5](https://tex.z-dn.net/?f=-4%2B4y-4z%2By-2z%3D5)
![5y-6z-4=5](https://tex.z-dn.net/?f=5y-6z-4%3D5)
![y=\frac{6z+9}{5}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B6z%2B9%7D%7B5%7D)
Substitute
and
into the third equation:
![\frac{-41z-54}{5}+3=-16](https://tex.z-dn.net/?f=%5Cfrac%7B-41z-54%7D%7B5%7D%2B3%3D-16)
![-41z-54=-95](https://tex.z-dn.net/?f=-41z-54%3D-95)
![z=1](https://tex.z-dn.net/?f=z%3D1)
Substitute
into
:
![y=3](https://tex.z-dn.net/?f=y%3D3)
Plug in y and z values into
:
![x=1](https://tex.z-dn.net/?f=x%3D1)
Answer:
? what are the answers from 1 and 2?
Step-by-step explanation:
Answer: 0
Step-by-step explanation:
In this equation 0/y would equal 0, no matter what y is. 0/y means that there's 0 items out of y items (ex: substitute y with 2, it would be 0/2). Beginning with 1*0 (one times zero) the answer there would be 0. Since we already know that 0/y equals 0, the rest of the equation would be 0 - 0 which would equal to 0. Hope this explanation helps :)